Energy Efficiency Management Module - João Pedro da Silva Almeida (2017)
The search of energy consumption and cost reductions, in organizations, led to the implementation of energy management systems, that allowed automatic consumption monitoring. However, consequence of the harsher legislation, the search for cost reduction and the energy policies focused on the environment protection, there is a growing demand for tools, integrated in management systems, that support the pursuit of energy efficiency improvement goals. In this sense, this master dissertation project intends to perform an analysis of the current available market solutions, the idealization and specification of a management module compatible with the standard, that allows for main energy uses examination according to the norm, creating improvement plans and evaluating their results. Finally, within the context of this dissertation, part of the 50001 module will be developed so that the concepts, specification and architecture can be validated.